Loneliness, Escapism, and Identification With Media Characters: An Exploration of the Psychological Factors Underlying Binge-Watching Tendency - Gabbiadini, Alessandro; Baldissarri, Cristina; Valtorta, Roberta Rosa; Durante, Federica; Mari, Silvia (Frontiers in Psychology, 2021)
Nowadays, binge-watching (i.e., watching multiple episodes of a TV-series in one session) has become a widespread practice of media consumption, raising concerns about its negative outcomes. Nevertheless, previous research has overlooked the underlying psychological mechanisms leading to binge-watching. In the present work, we investigated some of the psychological variables that could favor binge-watching tendencies in a sample of TV-series viewers (N=196). To this aim, psychological determinants of problematic digital technologies usage (i.e., feelings of loneliness), as well as some of the mechanisms related to the enjoyment of media contents (i.e., escapism and the identification with media characters), were considered as predictors of the tendency to binge-watch. Results indicated that higher feelings of loneliness were associated with higher levels of problematic digital technologies usage. Additionally, direct and indirect effects showed that only escapism – out of the four dimensions measuring the problematic use of internet-related technologies - predicted participants’ stronger identification with media characters, which in turn promoted greater binge-watching tendencies. Overall, we suggest that binge-watching could be interpreted as a coping strategy for media-escapists, who enjoy TV-series as a privileged online space in which the need to escape finds its fulfillment, allowing them to manage loneliness by identifying with a fictitious character.